Elastic moduli of boron nitride, aluminium nitride and gallium nitride nanotubes using second generation reactive empirical bond order potential. Issue 1 (8th June 2015) - Kumar, Dinesh; Verma, Veena; Dharamvir, Keya; Bhatti, H S
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to study elastic properties of III-V nitride nanotubes (NNTs) using second generation (REBO) potential. Design/methodology/approach – In the present research paper elastic properties of BN, AlN and GaN nanotubes have been investigated, using the second generation REBO potential by Brenner and co-workers, which is a bond order potential earlier used for carbon nanostructures successfully. In the present calculation, the same form of potential is used with adjusted parameters for h-BN, h-AlN and h-GaN. In all these cases the authors have considered graphite like network and strongly polar nature of these atoms so electrostatic forces are expected to play an important role in determining elastic properties of these nanotubes. The authors generate the coordinates of nanotubes of different chirality's and size. Each and every structure thus generated is allowed to relax till the authors obtain minima of energy. The authors then apply the requisite compressions, elongations and twists to the structures and compute the elastic moduli. Young's Modulus, Shear Modulus and Poisson's ratio for single-walled armchair and zigzag tubes of different chirality's and size have been calculated. The computational results show the variation of Young's Modulus, Poisson's ratio and Shear Modulus for these NNTs with nanotube diameter. The results have been compared with available data, experimental as well as theoretical. Findings – The authors have calculated bond length, cohesive energy/bond, Strain energy, Young's Modulus, Shear Modulus and Poisson's ratio. Originality/value – To the best of the knowledge this work is the first attempt to study elastic properties of III-V NNTs using second generation REBO potential